PENDIDIKAN KARAKTER DI STAIN PEKALONGAN - Tri Astutik Haryati; Miftahul Ula; Abdul Khobir (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2013)
State College of Islamic Studies of Pekalongan as an Islamic college under the Ministry of Religious Affairs has a great responsibility and a strategic role in developing character building. It is because STAIN is an institution of higher education that produces many Muslim intelectuals and religionists. Based on that, this study was aimed to understand in depth about the role of the institution, the learning system, and the programs that are being done by the Research and Community Center of the institution (P3M STAIN Pekalongan) in developing character building. Phenomenological approach was used to understand the subjective aspect of persons' behavior and the conceptual nature of them. The result showed that the character building in STAIN Pekalongan seemed to be representative enough. But in practice, however, got a very big challenge, either from inside education environment or from outside.